THE IMPLEMENTATION OF MINIMUM COMPETENCY ASSESSMENT (AKM): OPPORTUNITIES AND CHALLENGES FOR ENGLISH TEACHERS - Auliya, Prativi Khilyatul (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2022)
Minimum Competency Assessment (AKM) is the new evaluation system to monitor the education quality in Indonesia. Its implementation starts from 2021. This new system focuses on students’ literacy and numeracy skill without assessing any of school subjects. The purpose of this study is to investigate 1) the opportunities of AKM for English teachers and 2) the challenges of AKM for English teachers. Survey research with descriptive qualitative approach is used on this study. As instruments, online questionnaire and interview is utilized. The findings show that there are four opportunities; 1) English teachers tend to be happier, 2) English teachers are freer to implement certain teaching method, 3) English teachers could focus more on the use of English, not on test completion, and 4) English teachers could give more attention for students’ literacy. In addition, there are five challenges; 1) socialization about AKM is not yet done comprehensively, 2) most of students have less reading motivation, 3) it’s quite hard to connect English with numeration aspect, 4) teachers are having less experience in creating HOTS questions, 5) less skilful teacher in using technology.